Proceedings of XXIII International Workshop on Deep-Inelastic Scattering — PoS(DIS2015) 2016
DOI: 10.22323/1.247.0131
|View full text |Cite
|
Sign up to set email alerts
|

Forward-backward asymmetries of $(B^-, B^+)$, $(\Lambda_b, \bar\Lambda_b)$ and $(\Lambda,\bar\Lambda)$ in $p\bar p$ collisions at D0

Abstract: Forward-backward asymmetries of (B − ,B +),(Λ b ,Λ b) and (Λ,Λ) in pp collisions at D0.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
35
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(36 citation statements)
references
References 7 publications
1
35
0
Order By: Relevance
“…Introduction. Over the past several years, the twin Advanced LIGO observatories [1] have been detecting gravitational wave (GW) signals from coalescences of compact binary objects on a regular basis [2][3][4][5][6]. Meanwhile Advanced Virgo [7] has joined the global network of detectors, leading to further detections, including a binary neutron star inspiral [8].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Introduction. Over the past several years, the twin Advanced LIGO observatories [1] have been detecting gravitational wave (GW) signals from coalescences of compact binary objects on a regular basis [2][3][4][5][6]. Meanwhile Advanced Virgo [7] has joined the global network of detectors, leading to further detections, including a binary neutron star inspiral [8].…”
mentioning
confidence: 99%
“…Thanks to these observations, general relativity (GR) has been subjected to a range of tests. For the first time we had access to the genuinely strong-field dynamics of the theory [2,4,5,10,11]. Possible dispersion of gravitational waves was strongly constrained, leading to stringent upper bounds on the mass of the graviton and on local Lorentz invariance violations [5,10,11].…”
mentioning
confidence: 99%
“…Such possibility may be related to the heavy binary neutron star mergers observed in GW190425 (Abbott et al 2020), which is heavier than any known binary neutron stars in our galaxy 4 . It was suggested that tight binaries exist in our galaxy, because shortperiod binaries are difficult to observe with current methods.…”
Section: Spin Precession Of Frb 180916j0158+65mentioning
confidence: 82%
“…It was suggested that tight binaries exist in our galaxy, because shortperiod binaries are difficult to observe with current methods. On the other hand, if this heavy neutron star pair is formed within a fast-merging channel, this may also account for the potential bias towards detection (Abbott et al 2020;Romero-Shaw et al 2020). Safarzadeh et al (2020) argued that this leads to theoretical difficulties as traditional fastmerging channels (such as case BB unstable mass transfer) are unable to produce as frequent neutron star mergers.…”
Section: Spin Precession Of Frb 180916j0158+65mentioning
confidence: 99%
See 1 more Smart Citation